Photopromoted oxidative dissolution of stibnite. (October 2015) - Hu, Xingyun; He, Mengchang; Kong, Linghao
Highlights: Light irradiation promoted the dissolution of stibnite. The oxidation of Sb(III) and H2 S induced the increase of dissolution of stibnite. Key photo-oxidants are O2, O 2 -, OH and h vb + . A photocatalytic oxidation mechanism for stibnite dissolution was proposed. This study help to elucidate the release pathway of antimony into the environment. Abstract: Light irradiation plays an important role in the oxidative dissolution of Sb2 S3 . A qualitative mechanism was proposed through simulated experiments to describe the dissolution reaction under various ambient conditions, specifically darkness/light and aerobic/anaerobic conditions. The pH-dependent solubility of Sb2 S3 (s) and photo-induced oxidative dissolution are two types of reaction mechanisms. The oxidation of Sb(III) and its sulfides by light irradiation induce the prompt dissolution of Sb2 S3 . Photo-oxidants in the form of hydroxyl radicals ( OH ), superoxide anion free radicals ( O 2 - ) and photo-generated holes h vb + were produced in the photo-induced oxidative dissolution reaction of Sb2 S3 . Among these, O2 and O 2 - are the most significant oxidants. The main oxidation products of Sb2 S3 are Sb(V), S 0 and S 2 O 3 2 - . This study may help elucidate the geochemistry and fate of antimony in the environment.